RETRACTED: Motivasi Belajar siswa SMK N 1 Payakumbuh dalam Pembelajaran Renang - Endi Ahmad; James Tangkudung; Yasep Setia Karna Wijaya; Widiastuti (UIR Press, 2018)
This article has been withdrawn at the request of the Chief Editor. The reason for the withdrawal is that this article also published in the Journal Physical Education, Health and Recreation link: (https: //jurnal.unimed.ac.id/2012/index.php/jpehr/article/view/ 9557). The condition for submitting a work for publication is that the author explicitly states that all of his works are original and have not appeared in publications elsewhere. We apologize to journal readers that this was not detected during the delivery process.